A Comparison of Single- and Multiparametric MRI Models for Differentiation of Recurrent Glioblastoma from Treatment-Related Change - Eisenhut, Felix; Engelhorn, Tobias; Arinrad, Soheil; Brandner, Sebastian; Coras, Roland; Putz, Florian; Fietkau, Rainer; Dörfler, Arnd; Schmidt, Manuel (Diagnostics, 2021)
To evaluate single- and multiparametric MRI models to differentiate recurrent glioblastoma (GBM) and treatment-related changes (TRC) in clinical routine imaging. Selective and unselective apparent diffusion coefficient (ADC) and minimum, mean, and maximum cerebral blood volume (CBV) measurements in the lesion were performed. Minimum, mean, and maximum ratios(CBV) (CBVlesion to CBVhealthy white matter) were computed. All data were tested for lesion discrimination. A multiparametric model was compiled via multiple logistic regression using data demonstrating significant difference between GBM and TRC and tested for its diagnostic strength in an independent patient cohort. A total of 34 patients (17 patients with recurrent GBM and 17 patients with TRC) were included. ADC measurements showed no significant difference between both entities. All CBV and ratios(CBV) measurements were significantly higher in patients with recurrent GBM than TRC. A minimum CBV of 8.5, mean CBV of 116.5, maximum CBV of 327 and ratio(CBV) (minimum) of 0.17, ratio(CBV) (mean) of 2.26 and ratio(CBV) (maximum) of 3.82 were computed as optimal cut-off values. By integrating these parameters in a multiparametric model and testing it in an independent patient cohort, 9 of 10 patients, i.e., 90%, were classified correctly. The multiparametric model further improves radiological discrimination of GBM from TRC in comparison to single-parameter approaches and enables reliable identification of recurrent tumors.
CRIS-Team WoS Importer:2022-01-07

Classification of primary cerebral lymphoma and glioblastoma featuring dynamic susceptibility contrast and apparent diffusion coefficient - Eisenhut, Felix; Schmidt, Manuel; Putz, Florian; Lettmaier, Sebastian; Fröhlich, Kilian; Arinrad, Soheil; Coras, Roland; Lücking, Hannes; Lang, Stefan; Fietkau, Rainer; Dörfler, Arnd (Brain Sciences, 2020)
This study aimed to differentiate primary central nervous system lymphoma (PCNSL) and glioblastoma (GBM) via multimodal MRI featuring radiomic analysis. MRI data sets of patients with histological proven PCNSL and GBM were analyzed retrospectively. Diffusion-weighted imaging (DWI) and dynamic susceptibility contrast (DSC) perfusion imaging were evaluated to differentiate contrast enhancing intracerebral lesions. Selective (contrast enhanced tumor area with the highest mean cerebral blood volume (CBV) value) and unselective (contouring whole contrast enhanced lesion) Apparent diffusion coefficient (ADC) measurement was performed. By multivariate logistic regression, a multiparametric model was compiled and tested for its diagnostic strength. A total of 74 patients were included in our study. Selective and unselective mean and maximum ADC values, mean and maximum CBV and ratioCBV as quotient of tumor CBV and CBV in contralateral healthy white matter were significantly larger in patients with GBM than PCNSL; minimum CBV was significantly lower in GBM than in PCNSL. The highest AUC for discrimination of PCNSL and GBM was obtained for selective mean and maximum ADC, mean and maximum CBV and ratioCBV. By integrating these five in a multiparametric model 100% of the patients were classified correctly. The combination of perfusion imaging (CBV) and tumor hot-spot selective ADC measurement yields reliable radiological discrimination of PCNSL from GBM with highest accuracy and is readily available in clinical routine.
CRIS-Team Scopus Importer:2020-12-04
Keywords: ADC; DSC; Glioblastoma; MRI; Multimodal; Primary central nervous system lymphoma

Technical Modification of Amygdalo-Hippocampectomy in Temporal Lobe Epilepsy Surgery to Further Reduce Severe Neurological Complications: A Clinical-Anatomical Study - Roessler, Karl; Kasper, Burkhard; Coras, Roland; Arinrad, Soheil; Scholz, Michael; Hamer, Hajo; Blümcke, Ingmar; Buchfelder, Michael (World Neurosurgery, 2018)
BACKGROUND: Temporal lobe resection (TLR) including amygdalohippocampectomy (AHE) is the most frequent performed procedure in epilepsy surgery. Owing to the close anatomic relationship of the mesial temporal structures and the midbrain and choroidal fissure, the incidence of severe complications, such as postoperative stroke, is as high as 2.5%. METHODS: We developed a modification of the classical technique for AHE that involves entering the choroidal fissure early via the anterior part of the frontomesial temporal horn cleft to identify the crus cerebri, posterior cerebri artery, and oculomotor nerve. In a second step, after visualization of the cleavage plane between the midbrain and middle cerebral artery, the uncus and amygdala are removed. RESULTS: A total of 81 patients (47 females and 34 males; mean age at surgery, 40 years) underwent TLR including AHE with our surgical modification to treat heterogeneous pathologies. The cohort included 45 patients with hippocampal sclerosis, 11 with ganglioglioma, 2 with dysembryoplastic neuroepithelioma, 2 with diffuse glioma, and 21 with other pathologies, including cavernoma, scar tissue, and mild cortical dysplasia, among others. In all patients, anterior temporal resection was performed via AHE using our modified technique. Seizure outcome was favorable after a mean follow-up of 27 months (range, 3-56 months); 64% of the patients were completely seizure-free (Engel class 1A), and 75% had an Engel class 1 outcome. There was no mortality or permanent severe neurologic complications, and the rate of surgical complications was 3.7%. CONCLUSIONS: Our modified AHE technique is associated with a low rate of complications in TLR for medically refractory temporal lobe epilepsy, and helps avoid permanent severe neurologic complications.
EVALuna2:34587